Análise da cadeia cinética em atletas arremessadores com e sem dor no ombro - Pogetti, Lívia Silveira (2017)
Shoulder pain is quite prevalent in throwing athletes. The high incidence may be the result of a deficit of the integrated action of the kinetic chain during the throwing movement. There is lack of studies that have evaluated the components of the kinetic chain in throwers with and without shoulder pain. Researches in this area are important since it could provide knowledge about the kinetic chain components in this population, in order to obtain better treatment and evaluation protocols. In this way, the purposes of the thesis were (1) to evaluate the muscular performance of the kinetic chain of throwing athletes with and without pain in the shoulder; (2) to evaluate the function of the shoulder, trunk, pelvis and lower limb in this population; and (3) to analyze the correlation between these variables and the muscular performance in athletes with shoulder pain. Endurance time test and maximum voluntary isometric contraction were used to evaluate the trunk flexors, extensors and lateral flexors muscles. Isometric contraction was measured by handheld dynamometer (Lafayette Instrument Company, Lafayette, IN). Isokinetic dynamometer Biodex Multi-Joint System 3 (Biodex Medical System Inc., NY, USA) in the concentric mode was used to evaluated peak torque of external and internal rotation of the shoulder at 90º/s, 180º/s and 240º/s. Questionnaires, shoulder satisfaction level and range of motion were used to measure the shoulder function, while the modified star excursion balance test (SEBT) and transverse pelvic alignment test were used to assess the hip, trunk and lower limb function. In general, the results showed that throwing athletes with shoulder pain presented shorter endurance time of the trunk lateral flexors and balance, and worse shoulder function compared to asymptomatic athletes. However, shoulder pain does not seem to affect the development of shoulder isokinetic peak torque and ROM compared to athletes without shoulder pain. Furthermore, the results showed the weak to moderate positive correlations between internal and external rotation of the arm and endurance and isometric strength of the trunk flexors. Peak torque of the shoulder was not correlated to transverse pelvic alignment. Such results support the kinetic chain theory based on the interdependence of segments to generate and transfer of forces during functional movements. In addition to suggesting that exercises that work neuromuscular control of the lower limb and isometric strength and endurance, particularly for the trunk lateral flexor and flexor muscles should be stimulated in throwers with shoulder pain as part of the rehabilitation plan.